Tri-dimensional measurements to evaluate dimensional alterations in gypsum patterns for complete dentures - Wildes da C. Monteiro; Christiano A. de L. Corradi; Saide S. Domitti; Simonides Consani (Brazilian Dental Science)
The use of machines to measure specifics points in the patterns, these points transference to a tri-dimensional design program and the areas math calculation, by the solids produced in that program are an efficient alternative to verify and after compare the dimensional variations that occurs in gypsum patterns, related of the moulding materials. The use of this technology was fundamental for determinating dimensional variation's accuracy, that in most case are too acute and hard to be determinated and compared. The present paper proved how important is the use of method to get tri-dimensional points, to obtain the respectives digital solids and areas and volumes calculation by finite element method. These concepts are important, since they strongly contribute for the result accuracy about dimensional variation, as mathematic treatment was made in three dimensions (breadth, length and height) on the pattern in study.